Visible-Light-Driven Transformations of Phenols via Energy Transfer Catalysis - Fischer, Jérôme; Nun, Pierrick; Coeffard, Vincent (Synthesis, 2020)
In the past decade, the field of visible-light-mediated photocatalysis has been particularly thriving by offering innovative synthetic tools for the construction of functionalized architectures from simple and readily available substrates. One strategy that has been of interest is energy transfer catalysis, which is a powerful way of activating a substrate or an intermediate by using the combination of light and a relevant photosensitizer. This review deals with recent advances in energy transfer catalysis applied to phenols, which are ubiquitous in chemistry both as starting materials and as high-added-value products. Processes involving energy transfer from the excited photosensitizer to ground state oxygen and to phenol-containing substrates will be described.1 Introduction2 Intermolecular Processes2.1 Reactions with Singlet Oxygen2.2 [2+2] Cycloadditions3 Intramolecular Transformations4 Conclusions and Outlook
Keywords: photochemistry; phenol; dearomatization; cycloaddition; singlet oxygen